No association between smoking and sentinel lymph node metastasis and survival in cutaneous melanoma. (30th July 2019) - Tejera‐Vaquerizo, A.; Descalzo‐Gallego, M.A.; Traves, V.; Requena, C.; Bolumar, I.; Pla, A.; Nagore, E.
Abstract: Background: There is little evidence that smoking is associated with metastasis in patients with cutaneous melanoma. Objective: Using a propensity score matching analysis, we assessed whether smoking was associated with a higher rate of sentinel lymph node (SLN) metastasis and worse survival in these patients. Methods: Retrospective cohort study at a referral hospital for melanoma. We studied 762 patients with known smoking status from the melanoma database of the Instituto Valenciano de Oncología who underwent SLN biopsy between 1 January 2000 and 31 December 2016. The patients were matched by smoking status. The matching procedure was implemented using three logistic regression models featuring never vs. former smokers, never vs. current smokers and former vs. current smokers. The study outcomes were disease‐free survival (DFS), melanoma‐specific survival (MSS), overall survival (OS) and SLN status. Results: The following groups were formed based on the propensity matching scores: 114 pairs of smokers vs. never smokers, 113 pairs of smokers vs. former smokers and 174 pairs of never smokers vs. former smokers. Smoking status was not associated with SLN metastasis or with DFS, MSS or OS in any of the three groups. Conclusion: Smoking does not influence SLN metastasis or survival in patients with cutaneous melanoma. Abstract : Linked Commentary: R. Stadler. J Eur Acad Dermatol Venereol 2019; 33 : 2219–2220. https://doi.org/10.1111/jdv.16020 .